Pengetahuan Guru terhadap Penerapan Perilaku Hidup Bersih dan Sehat - Sonya Balkis; Agus Ramon; Afriyanto Afriyanto; Nopia Wati (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the relationship between teachers' knowledge of PHBS and its implementation at SLB Negeri 1, Bengkulu City. The research method used a quantitative approach with a cross-sectional design. The results showed that most teachers had high knowledge, and PHBS implementation was also predominantly in the high category. A bivariate test yielded a p-value of 0.002 (p < 0.05), indicating a significant relationship between knowledge level and PHBS implementation. In conclusion, the better the teachers' knowledge, the more optimal the implementation of PHBS in schools. Therefore, improving knowledge through training and providing PHBS support facilities is highly recommended to support the realization of healthy schools.   Keywords: Teachers, PHBS, Implementation, Knowledge, Healthy Schools